Surgical Management of Bhagandara by IFTAK Technique Along with Aragwadhadi Varti - Piyush Ranjan Parhi; Balendra Singh; Satrupa Nirmal; Dheeraj Singh Baghel; Subodh Kumar Sahu; Dileep Diwaker (AYUSHDHARA, 2025)
Fistula is a condition in which two epithelial surfaces communicate abnormally. When a communication is established between anal canal and perineal region that condition is called as fistula-in-ano. The track is typically lined with unsightly granulation tissues. The primary cause of this condition is improperly treated crypto glandular infection. Over the advancement of time the Ksharasutra is still the best choice among treatment modalities available for Fistula-in-ano because of lesser complications like recurrence and incontinence. Despite all these advantages, there are still certain drawbacks such as discomfort, prolonged periods of anxiety, increased hospital visits, extended treatment duration, and significant post-operative scarring, among others. IFTAK (Interception of Fistulous tract with application of Ksharasutra) is a novel advanced Ksharasutra technique thus making it more convenient to patient as well as to exclude the drawbacks of conventional method. Further using Aragwadhadi varti along with the above said technique lead to better healing of the leftover portion of the track. Here in this case, IFTAK is done under Local anaesthesia. Kshara sutra was changed upto 4 weeks and Aragwadhadi varti applied for 10 times. The fistula healed completely in 2 months. This study revealed an early complete remission of the fistulous tracts by IFTAK method and Aragwadhadi varti, When compared with the conventional Kshara sutra method. According to the length, the conventional method takes 15-20 weeks whereas in this study it took much less time. And during followup no recurrence was noted. Therefore, the IFTAK technique combined with Aragwadhadi varti was deemed highly effective due to its time-saving properties and reduced scar and fibrosis.